2004
DOI: 10.1007/s10147-003-0378-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of treatment failure following radiotherapy with combination chemotherapy for patients with high-risk stage IIB cervical carcinoma

Abstract: Although systemic chemotherapy was administered concurrently with radiotherapy, the incidence of pelvic failure was highest, followed by paraaortic lymph node metastases, in patients with stage IIB cervical carcinoma with high-risk factors, following radiotherapy with combination chemotherapy. To evaluate the patterns of treatment failure in patients with stage IIB cervical carcinoma with high-risk factors following radiotherapy given concurrently with combination chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
2
19
0
2
Order By: Relevance
“…Park et al 69 reported that, of 349 patients treated with concurrent radiotherapy and chemotherapy, treatment failure occurred in 79 patients (22.6%). Forty-six (13.2%) had persistent disease and 33 (9.5%) had recurrent disease.…”
Section: Pattern Of Failure In Node-positive Cervical Cancermentioning
confidence: 98%
See 2 more Smart Citations
“…Park et al 69 reported that, of 349 patients treated with concurrent radiotherapy and chemotherapy, treatment failure occurred in 79 patients (22.6%). Forty-six (13.2%) had persistent disease and 33 (9.5%) had recurrent disease.…”
Section: Pattern Of Failure In Node-positive Cervical Cancermentioning
confidence: 98%
“…Pelvic failure was the most frequent failure in the group with tumors sized 4 cm or more, whereas, for the positivelymph-node group, distant metastasis was most frequent and metastases to paraaortic lymph nodes was common. 69 Aoki et al 70 reported the failure pattern in 161 patients with lymph-node negative stage Ib-II cervical cancer treated with radical hysterectomy and postoperative radiotherapy. For this group of patients, deep cervical stromal invasion was the only independent prognostic factor, and the rate of recurrence in pelvic and distant sites was almost equal.…”
Section: Pattern Of Failure In Node-positive Cervical Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…In an analysis of the pattern of failure, Park et al [24] could demonstrate the correlation between lymph node recurrence and distant metastases in patients with stage IIB cervical cancer: 19% of the patients had pelvic nodal failure after chemoradiation. 11.6% of the patients with pelvic failure developed distant metastases compared to 6.5% of the patients with locally controlled tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where there is only 1 positive node, no adverse effect on patient survival has been observed, according to certain authors (16,17). Inoue and Morita (14) reported on the effect of the number of positive LNs on stage IB-IIB cervical cancer.…”
Section: Progression-free Survivalmentioning
confidence: 96%